Adventure stories - Hathaway, Jo; Irvine, Mark (Oxford Macmillan ELT, 2011)
This series of Readers containing original, unsimplified stories written by famous classic and modern writers, now features four new titles. All the collections come with substantial support material for each story, including a short summary, a description of major themes, pre-reading vocabulary activities, post-reading language and comprehension exercises, a literary analysis section and essay questions. "The Macmillan Literature Collections" will help ease students' transition from graded Readers to authentic reading, giving them the joy of feeling that they are finally reading and studying literature just as it was written.
To build a fire A fight with a cannon The old chief Mshlanga The adventure of the hansom cab The sun rises twice by Jack London. -- by Victor Hugo. -- by Doris Lessing. -- by Robert Louis Stevenson. -- by H.E. Bates.
Keywords: Children's stories; Adventure and adventurers -- Fiction; Short stories; Adventure stories; Short stories, English; Readers for new literates; English language -- Textbooks for foreign speakers; dventure and adventurers